An outcomes evaluation for the Allan Gray Orbis Foundation's Fellowship Programme - Cooksey, Cayla (Organisational Psychology, 2025)
This dissertation is based on an outcome evaluation of the Allan Gray Orbis Foundation's Fellowship programme. The Fellowship programme is an extracurricular entrepreneurial education programme that aims to develop high achieving individuals in their academic, personal, and entrepreneurial spheres. Students enter the programme in the first year of their degree and graduate the programme after four years. The evaluation was purposed to determine whether the programme achieves its intended outcomes from the perspective of its participants. This evaluation used qualitative methods to interview 14 past participants of the programme. Six of these participants completed the programme successfully, eight did not complete the programme. Interviews provided insight into what works and what does not work. The evaluation found that the Fellowship is successful in achieving most of its intended outcomes, specifically developing an entrepreneurial mindset and entrepreneurial intention, developing a sense of community and the value of collaboration, and advancing interests in responsible entrepreneurship. A finding that is unique to the Fellowship and is an emerging point of interest in the field of entrepreneurship relates to the ability of the programme design to develop an entrepreneurial mindset and entrepreneurial intention in participants with no express mindset or interest prior to participation. The evaluation provided insight into the challenges faced by high performing, low-socioeconomic-status South African students in the University space and in the cross-socioeconomic entrepreneurial and social spaces. The evaluation found that mentorship plays a key role in the programmatic and academic success of participants. Primary recommendations for the refinement of the Fellowship include the removal of academic success as an outcome, the reevaluation of renewal criteria in the context of high performing, low-SES students, the establishment of specific support structures of high performing, low-SES students transitioning to university, the reduction of the theoretical entrepreneurial curriculum, the maintenance of experiential entrepreneurial learning opportunities, training its mentors to support low-SES students and identify and address barriers to success early on, to find ways of reducing the elite and competitive experience of the programme that results from cross-socioeconomic engagements. This evaluation concludes that the Fellowship is a well-designed programme that aligns with best practice in entrepreneurship and introduces innovative methods for successfully developing high impact entrepreneurs in South Africa.